Pengaruh Fitur Personalisasi dan Trust Terhadap Loyalitas Konsumen Gen Z di Aplikasi Shopee (Studi Kasus Gen Z Kota Malang) - Cici Nurfia; Nur Hidayati; Andi Normaladewi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of personalization and trust features on the loyalty of Generation Z consumers on the Shopee app. The approach used was quantitative, employing a survey method, by distributing questionnaires to Generation Z Shopee users in Malang City. The research sample was determined using purposive sampling, with 65 respondents. The collected data were then analyzed using multiple linear regression with the aid of SPSS software.The results show that personalization and trust features simultaneously have a positive and significant influence on consumer loyalty. Partially, personalization features were shown to have a positive and significant influence on consumer loyalty, indicating that product recommendations and promotions tailored to user preferences can increase interest and encourage repeat purchases. Furthermore, trust also had a positive and significant influence on consumer loyalty, indicating that confidence in the platform's security and confidentiality plays a crucial role in building consumer loyalty. The findings of this study are expected to serve as a reference for e-commerce managers in designing effective strategies to increase consumer loyalty. Keywords: Personalization Features, Trust, Consumer Loyalty, Shopee.